2017
DOI: 10.5301/tj.5000640
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiotherapy in the Treatment of Renal Cell Cancer: Updated and Critical Review

Abstract: In the coming years, new studies will be published to confirm and increase the indications for use of RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In the treatment of rectal cancer, radiotherapy and chemotherapy are often used in combination, as chemotherapy often induces systemic toxicity (31). As technology advances, modern radiation therapy technology enables a high degree of conformity, including the use of computed tomography images to provide high precision and precise treatment, optimizing treatment planning (32,33); however, the limitation of radiation exposure remains an issue with radiotherapy. Therefore, the present study focused on increasing the sensitivity of cells to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of rectal cancer, radiotherapy and chemotherapy are often used in combination, as chemotherapy often induces systemic toxicity (31). As technology advances, modern radiation therapy technology enables a high degree of conformity, including the use of computed tomography images to provide high precision and precise treatment, optimizing treatment planning (32,33); however, the limitation of radiation exposure remains an issue with radiotherapy. Therefore, the present study focused on increasing the sensitivity of cells to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only 16.7% (n = 26) of patients stayed on pazopanib for the duration of the study. The investigator-assessed PFS in the Phase III COM-PAZ trial (10.5 months) and the global prospective observational PRINCIPLE study (10.3 months) were both 10.8 months (Fusco et al, 2017;Grünwald, 2016;.…”
Section: Pazopanibmentioning
confidence: 99%
“…However, a study from Rotterdam found that preoperative radiotherapy had no overall survival advantage over surgery. 24,25 Outcomes of radiotherapy after radical nephrectomy were evaluated in both prospective and retrospective studies. The latest stereotactic body radiotherapy (SBRT) technique uses multi-angle projection and focused beam technologies, which allow the targeting of specific tissues with a high dose of radiation without causing damage to normal tissues, meaning it can be applied to metastatic tumors that are relatively insensitive to radiotherapy.…”
Section: Treatmentmentioning
confidence: 99%